The X-ray Integral Field Unit at the end of the Athena reformulation phase - Peille, Philippe; Barret, Didier; Cucchetti, Edoardo; Albouys, Vincent; Piro, Luigi; Simionescu, Aurora; Cappi, Massimo; Bellouard, Elise; Cénac-Morthé, Céline; Daniel, Christophe; Pradines, Alice; Finoguenov, Alexis; et al. (Experimental Astronomy, 2025)
The Athena mission entered a redefinition phase in July 2022, driven by the imperative to reduce the mission cost at completion for the European Space Agency below an acceptable target, while maintaining the flagship nature of its science return. This notably called for a complete redesign of the X-ray Integral Field Unit (X-IFU) cryogenic architecture towards a simpler active cooling chain. Passive cooling via successive radiative panels at spacecraft level is now used to provide a 50 K thermal environment to an X-IFU owned cryostat. 4.5 K cooling is achieved via a single remote active cryocooler unit, while a multi-stage Adiabatic Demagnetization Refrigerator ensures heat lift down to the 50 mK required by the detectors. Amidst these changes, the core concept of the readout chain remains robust, employing Transition Edge Sensor microcalorimeters and a SQUID-based Time-Division Multiplexing scheme. Noteworthy is the introduction of a slower pixel. This enables an increase in the multiplexing factor (from 34 to 48) without compromising the instrument energy resolution, hence keeping significant system margins to the new 4 eV resolution requirement. This allows reducing the number of channels by more than a factor two, and thus the resource demands on the system, while keeping a 4’ field of view (compared to 5’ before). In this article, we will give an overview of this new architecture, before detailing its anticipated performances. Finally, we will present the new X-IFU schedule, with its short term focus on demonstration activities towards a mission adoption in early 2027
CRIS-Team Scopus Importer:2025-03-21
Keywords: Athena; Instrumentation; Micro-calorimeters; X-ray integral field unit; X-rays